2010
DOI: 10.1016/j.tetlet.2010.02.099
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed intermolecular [4C+3C] cycloaddition reactions

Abstract: In the presence of the N-heterocyclic carbene gold catalyst (NHC-AuIPr, 7), propargyl esters 1a-f and 13 undergo a [4C + 3C] cycloaddition reaction with cyclopentadiene and furan under mild conditions. The evidence suggests the formation of the seven-membered ring occurs by a direct cycloaddition process, rather than a stepwise cyclopropanation/Cope rearrangement sequence.The potent antiangiogenesis natural product family of cortistatins contain a center sevenmembered ring flanked by two six-membered rings. 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 30 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…From a mechanistic point of view, it is important to note that, in contradistinction to what has previously been reported [Eq. (6)],9a,b, 2i the present tandem cycloisomerization/Cope rearrangement does not involve the initial formation of a gold carbenoid of type 24 which could be trapped by a diene to furnish the intermediate divinylcyclopropane 25 (compare 6 and 24 ). This is a key difference with earlier work.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…From a mechanistic point of view, it is important to note that, in contradistinction to what has previously been reported [Eq. (6)],9a,b, 2i the present tandem cycloisomerization/Cope rearrangement does not involve the initial formation of a gold carbenoid of type 24 which could be trapped by a diene to furnish the intermediate divinylcyclopropane 25 (compare 6 and 24 ). This is a key difference with earlier work.…”
Section: Methodsmentioning
confidence: 79%
“…2e More recently, electrophilic platimum(II) and gold(I) species have also shown their catalytic potential to produce 1 by a [4+3] cycloaddition between an allene and a diene [Eq. (1)] 2fi …”
Section: Methodsmentioning
confidence: 99%
“…[17] In contrast, when 1,4-dienes are used, the cyclopropyl system undergoes a goldcatalyzed Cope rearrangement to deliver the cis-2,3-disubstituted cycloheptenyl acetates 4 (Scheme 2; path b). [11] A boatlike transition state is proposed in this case to account for the observed cis relative stereochemistry.…”
Section: -Methoxy-4-(prop-1-en-2-yl)benzene (G) (Z)-1-methoxy-4-(prmentioning
confidence: 89%
“…[10] We envisioned that a reaction sequence involving propargyl esters and dienes could be orchestrated such that gold not only catalyzed the 1,2-acetoxy migration and subsequent cyclopropanation, but could also reactivate the in situ generated vinyl acetate, thereby triggering a formal homo-Cope rearrangement to give sevenmembered rings in a straightforward manner (Scheme 1; path a). [11] Furthermore, if alkenes instead of dienes were used, highly substituted cyclopentenyl acetates could be obtained upon cyclopropyl ring opening (Scheme 1; path b). Herein, we report the realization of these concepts and an application in the formal enantioselective synthesis of marine secondary metabolites frondosins A and B.…”
mentioning
confidence: 99%
“…However, significant progress has been made in the last 4 years. While the development of an intermolecular [4 + 3] cycloaddition between allenes and dienes remains elusive, neither in a racemic nor enantioselective fashion [69], it has been shown that allenamides [70] or allenyl ethers [71] participate as two-carbon atom components in several gold-catalyzed [4 + 2] cycloadditions with dienes. The racemic version of the reaction between allenamides and dienes, which is efficiently promoted by AuCl or the cationic gold catalyst Au9 /AgSbF 6 , was translated into a enantioselective version by using a novel chiral gold complex Au14 , featuring a triazole unit embedded in a rigid axially chiral cyclic frame (Scheme 11) [72].…”
Section: Reviewmentioning
confidence: 99%